PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PAPAN UTAMA (Yang Terdaftar Dalam Bursa Efek Indonesia Tahun 2014-2018) - Dika Zanuar Virgantara (Faculty of Economics and Business | Universitas Diponegoro, 2020)
Maximizing firm value is the main goal of the firm. The high value of the firm indicates that the firm is able to maintain business continuity and can improve the welfare of shareholders. So that investors are interested in investing their capital in firm’s that have high firm value. Several previous studies have shown different results regarding the value of the company. Therefore this study was conducted to re-examine the theory of the firm value, and to determine the effect of company size, leverage, and profitability on the value of the main board companies listed on the Stock Exchange in the 2014-2018 period.This study uses a causal associative method with a quantitative approach, the data used are secondary data from the reports of the main board firms listed on the Indonesia Stock Exchange in the 2014-2018 period obtained by 107 firms with purposive sampling techniques and analyzed using eviews 10. Data testing techniques used is descriptive statistical analysis, classic assumption test, correlation test, regression test, coefficient of determination analysis, and hypothesis testingThe results of the analysis show that the firm size variable produces a tcount (1.222) <ttable(1.974), and a significant value (0.221> 0.05) it means that the firm size partially has no effect on the firm value. Leverage variable produces a tcount (6,020)> ttable(1,974), and a significant value (0,00 <0.05), it means that leverage partially has a significant effect on the firm value. The profitability variable produces a tcount(12,965)> ttable(1,974), and a significant value (0,00 <0.05), it means that profitability has a partially significant effect on firm value. From testing all the independent variables simultaneously obtained fcount(61.079)> ftable(2.62), and the level of significance (0.00 <0.05). This shows simultaneously the variables of firm size, leverage, and profitability together affect of the firm value main board contained on the Indonesia Stock Exchange period 2014-2018.